Incidence and risk factors of intrauterine adhesions after myomectomy - Pietro Bortoletto, M.D., M.Sc; Kimberly W. Keefe, M.D; Emily Unger, M.D; Eduardo Hariton, M.D., M.B.A; Antonio R. Gargiulo, M.D (Elsevier, 2022)
Objective: To determine the incidence and risk factors for intrauterine adhesions (IUAs) after minimally invasive and open myomectomy and hysteroscopic myomectomy (HM). Design: Retrospective cohort study. Setting: University-affiliated fertility center. Patient(s): Patients aged ≥18 years undergoing robotic-assisted or conventional laparoscopic minimally invasive myomectomy, abdominal myomectomy, or HM between January 2007 and January 2017. Only patients who underwent uterine cavity evaluation within 12 months of surgery via hysteroscopy or hysterosalpingography were included. Patients were excluded if they had a history of IUA before myomectomy. Intervention(s): Not applicable. Main Outcome Measure(s): The primary outcomes of this study were the presence and severity of IUA. The secondary outcomes were the identification of risk factors for IUA formation. The severity of IUAs was scored by 2 investigators using a previously published grading system by March et al. Result(s): Of 1,315 patients who underwent myomectomy, 173 (13.2%) met the inclusion criteria. Intrauterine adhesions were identified in 9.3% of all patients, 75.0% of which were classified as minimal. The incidence of IUA did not vary by modality: 8.6%, minimally invasive myomectomy; 7.8%, abdominal myomectomy; and 11.8%, HM. There were no differences in incidence of IUA by the number or size of fibroids removed. Of patients with IUA, 87.5% had submucosal fibroids resected compared with 58.6% without IUA. Conclusion(s): The incidence of postoperative IUA in women undergoing myomectomy of any modality is relatively low (9.3%) and does not vary by modality alone. Most IUAs are of minimal degree. The presence of submucosal fibroids is associated with an increased risk of IUA in all modalities.